地域診断から地域経営診断へ - 海野 進 (Journal of Japan Management Diagnosis Association, 2010)
In regional consulting, such as wide-area commercial consulting, producing area consulting and regional commercial modernization programs which were conducted after 1970s, the main purpose was to grasp regional structures and the main target was the results/output of the activities. Such consulting were meant for regional programs and policies and their role was for the government in great measure. Since 1980s, due to lowered trust in the government, good governance has been reviewed and corporate management techniques, such as meritocracy and customer driven has been introduced. Under such circumstances, for the consulting in the age of local management where various subjects take actions toward regional operations and management, the following viewpoints should be necessary: ① local residents ② local management operations ③ outcome ④ feedback to various subjects. 70年代以降行われていた広域商業診断，産地診断，地域商業近代化計画などの地域診断においては，地域の構造を把握することが主眼，活動の結果・アウトプットを主な対象，地域計画・地域政策のためのものであり，ガバメントのためにという役割が大きかった。80年代以降，政府の信頼の低下などからガバナンスのあり方の見直しがすすめられ，業績主義，顧客主義という企業経営手法の導入などが進められてきた。このような中，多様な主体による地域運営・地域マネジメントに向けた活動が行われる地域経営の時代における診断は，①地域生活者，②地域経営活動，③成果，④多様な主体へのフィードバックという視点が必要である。